Answer:
15/22
Step-by-step explanation:
Let the angle of elevation be θ.
We have a right angled triangle with an opposite of 300.5 ft. (306 - 5.5) and an adjacent of 400 ft. Recalling SOH CAH TOA, tanθ = O/A.
tan(θ) = 300.5/400.
θ = tan^-1(300.5/400).
θ = 36.9°.
Hello!
The mean is the average. To calculate it you add up all the numbers, and divide by how many numbers there were. So for example, if you had 1 and 3, you would add them and divide by two since there were two numbers. We will calculate the mean of this data set below.
(11+21+16+7+10)=65
65/5=13
The mean of the data set is 13.
---------------------------------------------------------------------------------------
Now we need to find the median. To do so we have to first order all of the numbers from least to greatest.
7,10,11,16,21
Now we have to find the number in the middle of the data set.
11 is our median. (Note that when calculating the median with an even number of data points, you will find the mean of the two center numbers)
I hope this helps!
Answer:
Option A True
Step-by-step explanation:
we know that
The sum of the internal angles of the triangle is equal to ![180\°](https://tex.z-dn.net/?f=180%5C%C2%B0)
<u>In the triangle JKL</u>
m∠L=![180\°-90\°-27\°=63\°](https://tex.z-dn.net/?f=180%5C%C2%B0-90%5C%C2%B0-27%5C%C2%B0%3D63%5C%C2%B0)
so
The measurements of the angles of triangle JKL are ![27\°-90\°-63\°](https://tex.z-dn.net/?f=27%5C%C2%B0-90%5C%C2%B0-63%5C%C2%B0)
<u>In the triangle WXY</u>
m∠W=![180\°-90\°-63\°=27\°](https://tex.z-dn.net/?f=180%5C%C2%B0-90%5C%C2%B0-63%5C%C2%B0%3D27%5C%C2%B0)
so
The measurements of the angles of triangle WXY are ![27\°-90\°-63\°](https://tex.z-dn.net/?f=27%5C%C2%B0-90%5C%C2%B0-63%5C%C2%B0)
therefore
Triangle JKL and triangle WXY are similar by AAA ( The AAA postulate states that if you can prove that all three angles of two triangles are congruent, you can prove the two triangles are similar)
Answer:
a. y=x+1
b. x=-3
Step-by-step explanation:
a. slope= (6-4)/(5-3)=1
substitute (5,6) to y=1x+b; b=1
therefore, y=x+1
b. x=-3